EFFICACY OF DERMAROLLER VS TRICHLOROACETIC ACID (TCA) CROSS TECHNIQUE FOR TREATMENT OF ACNE SCARS - Sheraz, Samina; Gul, Mian Shahid; Kamal, Kashif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare efficacy of Derma Roller versus Trichloroacetic Acid (TCA) Chemical Reconstruction of Skin Scars (CROSS) technique for the treatment of acne scars.Study Design: Randomized control trial.Place and Duration of Study: Department of Dermatology, Maroof International Hospital Islamabad, from Mar to Sep 2020.Methodology: A total of 154 patients were sampled into two equal groups of 77 each, selected by non-probability consecutive sampling. Inclusion criteria was patients presenting with acne scars with duration >1 year, in the age range of 18-40 years, either gender and with acne scars on face only. The following patients were excluded from our study: patients with active acne or keloidal tendency, on oral retinoids and those having herpes labialis, group “A‟ patients were made to undergo four sessions of derma roller therapy at four weeks‟ interval each while group „B‟ had to undergo four sessions of Trichloroacetic Acid Chemical Reconstruction of Skin Scars technique at four weeks‟ interval each.Results: As per efficacy in both groups, 31 (40.25%) patients showed effective results in group A whereas in group B, 46 (59.74%) patients showed effective results, p-value 0.015.Conclusion: We therefore concluded that Trichloroacetic Acid Chemical Reconstruction of Skin Scars is comparatively better than Derma roller technique in the treatment of acne scars.